Pre-Late Wisconsinan age for part of the glaciolacustrine stratigraphy, lower Peabody valley, northern White Mountains, Gorham, New Hampshire - Fowler, Brian (Géographie physique et Quaternaire, 1999)
AbstractInterbedded till and glaciolacustrine deposits in the lower Peabody River Valley near Gorham, New Hampshire suggest multiple glacial advances occurred in the northern White Mountains. Previous workers disagreed on whether these advances were local or regional in nature, but thought they all occurred during the recessional phase of the Late Wisconsinan ice sheet. New stratigraphic and geomorphic reconnaissance, however, shows that a thick and regionally extensive till overlies this stratigraphy and that this till was emplaced by the last full-glacial episode to affect the region, the Late Wisconsinan glaciation. The stratigraphic position of this till makes the age of the underlying till and glaciolacustrine deposits pre-Late Wisconsinan and much older than previously assumed. This change in age assignment for part of the Peabody Valley stratigraphy supports the extension of the Illinoian-Late Wisconsinan "two-till" stratigraphy of central and southern New England into the region north of the White Mountain Highlands.